1990
DOI: 10.1126/science.247.4940.329
|View full text |Cite
|
Sign up to set email alerts
|

Far-Red Radiation Reflected from Adjacent Leaves: An Early Signal of Competition in Plant Canopies

Abstract: When individual seedlings of Datura ferox and Sinapis alba were transferred to populations formed by plants of similar stature, they responded with an increase in the rate of stem elongation. The reaction was detected within 3 days after transplanting and occurred well before shading among neighbors became important. This rapid response, which may be crucial for success in the competition for light, was reduced or abolished when individual internodes were "blinded" to the far-red radiation scattered by the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
457
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(474 citation statements)
references
References 19 publications
13
457
0
4
Order By: Relevance
“…However, this behavior can not be observed in soybean competition with hairy fleabane, because the increasing time interference decreased the soybean height. Changes in quality and light intensity, especially on red and far red wavelengths ratio incident on plants, affect the development of soybean cultivar (Ballaré et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…However, this behavior can not be observed in soybean competition with hairy fleabane, because the increasing time interference decreased the soybean height. Changes in quality and light intensity, especially on red and far red wavelengths ratio incident on plants, affect the development of soybean cultivar (Ballaré et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis was soon supported by a number of studies that demonstrated the following: (I) plants grown under full sunlight in the field respond to augmented FR radiation with increased elongation and apical dominance (Ballare et al 1987); (2) FR provides a reliable signal of the presence of neighbours well before plants experience a reduction in light availability (e.g. Ballare et al 1987); (3) the FR proximity signal is especially strong in the internodes (Ballare, Scopel & Sanchez 1989), which previous work had shown to be very sensitive to R:FR changes (Morgan, O'Brien & Smith 1980); (4) these changes in FR are quantitatively correlated with the density and proximity of the surrounding vegetation (Ballare et al 1989), and (5) filtering out FR from the light received by individual internodes in evenaged canopies can prevent the elongation response to crowding (Ballare et al 1990).…”
Section: Experimental Evidencementioning
confidence: 99%
“…Ballare et al (1987Ballare et al ( , 1990 proposed that FR radiation reflected by neighbouring plants played an important role as an early warning signal of competition in growing canopies. This hypothesis was soon supported by a number of studies that demonstrated the following: (I) plants grown under full sunlight in the field respond to augmented FR radiation with increased elongation and apical dominance (Ballare et al 1987); (2) FR provides a reliable signal of the presence of neighbours well before plants experience a reduction in light availability (e.g.…”
Section: Experimental Evidencementioning
confidence: 99%
“…The red (R) to far-red (FR) light ratio (R:FR) in dense stands is lower because of absorption by leaves of R light and reflection of FR (Ballaré et al, 1990). A low R:FR serves as a signal for shade or competition for light, and plants respond by inhibiting axillary bud outgrowth, growing taller, and flowering earlier to avoid the detrimental effect of shade.…”
mentioning
confidence: 99%